If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -18 = 23 Reorder the terms: -18 + x = 23 Solving -18 + x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + x = 23 + 18 Combine like terms: -18 + 18 = 0 0 + x = 23 + 18 x = 23 + 18 Combine like terms: 23 + 18 = 41 x = 41 Simplifying x = 41
| 10-18+3x=2x | | 3*x^2-16*x+15=0 | | -7.7x=61.6 | | x^2+5*x-7=0 | | 5x-x=-39 | | 6(x+2)-(2x-7)= | | 6y+4-2y=1+3y-7 | | x(28-x)=192 | | (8x+5)-(6x-7)= | | -4(4b+4)+(17b-3)=0 | | -90z-0.9=-100z+1.5 | | 90z-0.9=-100z+1.5 | | -7(5y+7)= | | 2.1q-5.2-3.5q=-2.4q-4.1 | | x^3-5x^2-11x-3=0 | | 4m+8=-8 | | 190=L+9(w) | | 5t-t-8=3t-6 | | 8z+z=8z+5 | | 42=2(l)(w) | | 2(2x+40)2x=680 | | 2(x+40)+x=680 | | 6+2(3m-4)-16m= | | 2(x+40)+2x=680 | | 5t-t-8=3t+6 | | -16+4=-2(x+3) | | -16+4=-2(2x+3) | | 1-3(y-5)=-5(y-2) | | 5(x-4)+6=2x+3(-4+x) | | 6.1x-3+x-1.9= | | r-8.5=-8.1 | | -2(7x-7)+1=-14x+15 |